Social Service Activities as an Effort to Increase Awareness and The Spirit of Sharing during The Holy Month of Ramadan - Maulida, De Lara Siti; Gunawan, Hevie Setia (Universitas Djuanda, 2025)
As it has been generally known that conducting Community Service (Pengabdian Kepada Masyarakat) is one of the obligations conducted by lecturer as three dharma of higher education. In addition to providing facilitate for community service, the Community Service offers institution an exciting opportunity to collaborate and make significant impacts in villages. Giving money or providing goods like food or clothing are common charitable activities. The focus of community service is on activities that directly benefit others. Regarding this concern, this community service is intended to increase social concern, especially in the month of Ramadhan which was conducted in the form of food and financial support for needy orphans and underprivileged at one of the foundations that cares and supports projects on orphans located in West Bandung regency. As it has been recognized that conducting social services especially in the month of Ramadhan is highly recommended as one of the positive activities conducted since obtaining rewards from Allah SWT. also benefits other individuals such as needy orphans and underprivileged among Muslims. The social service conducted at Al Muchlisin Miftahul Anshor Foundations aims to assist and provide spiritual and emotional support to the needy orphans and underprivileged society. During the activities, the children, society, community leaders, and the foundations' teachers have shown interest and enthusiasm. Thus, it is expected that this social service could benefit the parties involved such as the orphans, the needy society, the foundation itself, and so on.